Pentadbiran undang-undang Islam di Malaysia ([Kuala Lumpur] IKIM, 1997)
Institutionalization of Islamic law (syariah) in Malaysia; collected articles.
Includes bibliographical references and index.
Keywords: Islamic law -- Malaysia; Law -- Malaysia